Vernacularization of Sustainable Development Goals (SDGs): Diffusing Global Values in Indonesia’s Village Government - Tisnanta, HS.,; Putri, Ria Wierma; Khanza, Yuga Narazua; Pereira, Lenilde; Priyono, FX Joko (LAW REFORM, 2025)
This article explores how Indonesia’s village governments interpret and implement the Sustainable Development Goals (SDGs) through the process of vernacularization. Given Indonesia’s more than 81,000 villages, each with unique socio-cultural characteristics, localizing global norms is both a legal and practical challenge. The urgency lies in aligning global development frameworks with traditional village governance while maintaining local identities. This study aims to assess the implementation of Village SDGs and to evaluate vernacularization as a mechanism for translating global norms into culturally resonant practices at the grassroots level. Using a normative juridical method, this research analyzes legal documents, policy frameworks, and academic literature to identify patterns in SDG localization. Qualitative doctrinal analysis and thematic content review are applied to trace how global values are reinterpreted through local institutions and practices. Findings indicate that the 17 SDGs, along with Indonesia’s additional Goal 18 on adaptive village culture, align with existing local norms but require contextual adaptation. This is achieved through a three step vernacularization model involving translation, the role of vernacularizers, and framing, all grounded in a human rights based approach. The study concludes that vernacularization is essential to ensuring inclusive, culturally grounded, and sustainable implementation of the SDGs, reinforcing both universal values and local autonomy.